Básnický preklad na Slovensku po 1945 / Tłumaczenie poezji w Słowacji po 1945 r. (tłum. Marta Buczek) - Valcerová, Anna (Przekłady Literatur Słowiańskich, 2016)
The translation of poetry in Slovakia after 1945 After the clear dominance of naturalizing tendencies in the 1950s, when classic translations were preponderant, a predominance of up‑dated translations appeared. This was introduced by Feldek’s manifestation appearance in Mladá tvorba at the end of the 1950s and throughout the 1960s by the dominance of modern literature. This alternation of dominant tendencies is by no means mechanical, but it is also applicable in hindsight. Whereas in the period of Realism, naturalization tendencies (Kukučín, Hviezdoslav) seem dominant, the period of Modernism foregrounds those of exotization (Roy, Krasko). However, in the inter‑war period, exotization took turns with naturalization (Jesenský, Jesenská, Rázusová‑Martáková). J. Felix praises these translations although with respect to historization and modernization he is in favor of so‑called ‘vivification’, i.e. adapting translation to the epoch in which it originated, as well as the reader. Furthermore, Surrealists in the period of the Second World War and shortly before it seem to prefer modernization and exotization besides naturalizing translations. Thus, they bridge the period of naturalization from the 1950s to the 1960s when they became closer with the starting generation of Concretists. Again, after 1968 modernization was not pushed to the background mechanically; prime translations are still being modernized or up‑dated. After 1989, gradually after a wave of exotization, especially Americanization (shortly after the Revolution), attenuation of the modernizing and exoticizing methods in supreme translations, those of poems, in particular, may be observed, in contrast to what was referred to by Felix as vivification on a temporal axis and creolization, i.e. mixing of cultures, by Popovič. This is called an attenuated or classicist translation method; translation fulfils its basic role, it approximates to the style of a translated author and is at his service. Key words: modernization, exotization, creolization, naturalization, Slovak translation theory of poetry